Antiféminisme sur papier glacé - Auréline Cardoso (Glad!)
With his book The Rhetoric of Reaction: Perversity, Futility, Jeopardy published in 1991, economist Albert O. Hirschman offered an analysis of different rhetorics against social changes (French revolution, universal suffrage and welfare state). His frame of analysis and the three thesis (perversity, futility, jeopardy) he uncovered in reactionary speeches have often been used in researches about antifeminist rhetoric. This article intends to show how one can find that type of rhetoric in women’s magazines. The futility thesis is used in articles explaining why gender equality seems to be out of reach within heterosexual couples; the perversity thesis shapes an antifeminist rhetoric about how women’s self-reliance would, after all, harm women. The articles dealing with men convey many masculinist ideas, using the jeopardy thesis to speak in favour of a “masculinity crisis”.